The Influence of Brand Image, Price, and Distribution on the Decision to Purchase Toyota Spare Parts at PT Tasti Anugrah Mandiri - Sari Pujianti; Agus Sriyanto (Cahaya Abadi Publisher, 2026)
The objectives of this study were: to determine whether brand image influences the purchasing decision for Toyota spare parts at PT Tasti Anugrah Mandiri, to determine whether price influences the purchasing decision for Toyota spare parts at PT Tasti Anugrah Mandiri, and to determine whether distribution influences the purchasing decision for Toyota spare parts at PT Tasti Anugrah Mandiri, both partially and simultaneously. The population in this study were consumers who purchased Toyota spare parts (Toyota Genuine Parts) through PT TASTI Anugrah Mandiri. The research sample was obtained from consumers who had previously made transactions and completed a research questionnaire, with a total of 97 respondents. Data collection used a questionnaire with a Likert scale. The collected data were analyzed using SPSS. The results showed that partially, the Brand Image variable significantly influenced the Purchasing Decision, the Price variable significantly influenced the Purchasing Decision, and the Distribution variable significantly influenced the Purchasing Decision.